Regeneration of Engine Used Oils by Solvent Extraction - Sadraddin, Azad S.; Haji, Jalal A. (Iraqi Journal of Science, 2022)
The regeneration of used oil is one of the essential processes for economical, industrial and environmental targets. Used oil is rich of hydrocarbons, metals (such as: aluminium, chromium, copper, iron, lead, manganese, nickel, silicon and tin), gasoline, water and antifreeze. Due to the high increasing rate of the number of cars, there is a huge quantity of used oil. In this study, different brands of used oil were involved in extraction and adsorption processes as a regeneration process of these used oils. The optimum conditions were determined such as solvents composition, solvent: oil ratio, KOH concentration and temperature. The solvent mixture of 40% of petroleum ether, 11% of 1-butanol and 4% of 2-propanol has shown the best results in removing sludge. The 3:1 (solvent: oil) ratio may be considered as the best ratio practically and economically.